Magnetization and electronic structure of FeAs layered material - Noriza Ahmad Zabidi,; Hasan Abu Kassim,; Keshav N. Shrivastava, (Universiti Kebangsaan Malaysia, 2011)
Magnetic induction in the superconductor (B=H +4πM) in the zero field cooled samples (ZFC) is not equal to zero. Depending upon the chemical environment it has negative value in some and positive values in some others. In the field cooled samples, the magnetization becomes paramagnetic. We have calculated the band structure of one layer of FeAs lattice with spin polarized as well as unpolarized orbitals as a function of doping by Li atoms. For n number of Li atoms (n=0, 1,…, 4), we calculated the band gap at all of the k-points as well as the Fermi energy. The reduced normal state gap was found to lead to superconductivity.